Selectively Incapacitating Frequent Offenders: Costs and Benefits of Various Penal Scenarios - Blokland, Arie Aart Jan (Journal of quantitative criminology, 2007)
A small number of offenders are responsible for a disproportionate share of total crime. Policy makers have been seeking to reduce crime more efficiently by targeting corrections at these frequent offenders. Thus far, both macro- and micro-level research have yielded mixed results regarding the effects of these kinds of selective policies. The current study uses data from the Netherlands Criminal Career and Life-course Study to estimate the incapacitative effects of alternative selective prison policies. Using the rolling cohorts method, implementations of various penal scenarios differing in selection rate, sentence disparity and selective accuracy are simulated. Results show that it is hard for selective policies to yield a positive societal result: costs of imprisonment typically exceed benefits gained from crimes prevented.